A user-operated audiometry method based on the maximum likelihood principle and the two-alternative forced-choice paradigm. (June 2014) - Schmidt, Jesper Hvass; Brandt, Christian; Pedersen, Ellen Raben; Christensen-Dalsgaard, Jakob; Andersen, Ture; Poulsen, Torben; Bælum, Jesper
Abstract Objective: To create a user-operated pure-tone audiometry method based on the method of maximum likelihood (MML) and the two-alternative forced-choice (2AFC) paradigm with high test-retest reliability without the need of an external operator and with minimal influence of subjects' fluctuating response criteria. User-operated audiometry was developed as an alternative to traditional audiometry for research purposes among musicians. Design: Test-retest reliability of the user-operated audiometry system was evaluated and the user-operated audiometry system was compared with traditional audiometry. Study sample: Test-retest reliability of user-operated 2AFC audiometry was tested with 38 naïve listeners. User-operated 2AFC audiometry was compared to traditional audiometry in 41 subjects. Results: The repeatability of user-operated 2AFC audiometry was comparable to traditional audiometry with standard deviation of differences from 3.9 dB to 5.2 dB in the frequency range of 250–8000 Hz. User-operated 2AFC audiometry gave thresholds 1–2 dB lower at most frequencies compared to traditional audiometry. Conclusions: User-operated 2AFC audiometry does not require specific operating skills and the repeatability is acceptable and similar to traditional audiometry. User operated 2AFC audiometry is a reliable alternative to traditional audiometry.